Unconstrained temporal inconsistency checking of natural language in webpage. (27th August 2020) - Gan, Lin; Shu, Zhan; Li, Shijun
This paper discusses the problem called 'web temporal inconsistency', which refers to the ambiguity and conflict between the time webpages expressed and the actual time web users concerned about and understanding in the current situation. It is an important criterion of quality evaluation of network information, related to the timeliness and accuracy of webpage content. Huge quantities of pages have the problem, seriously affecting the user's understanding of content and decision-making. This paper analyses the problem of webpages, establishes the temporal inconsistency model and the method of measurement of unconstrained inconsistency which is one of the sub problems of web temporal inconsistency, and constructs the reasoning mechanism based on the web time axis. The experiments show the model is superior to the baseline.